Apelin peptides linked to anti‐serum albumin domain antibodies retain affinity in vitro and are efficacious receptor agonists in vivo. (10th April 2019) - Read, Cai; Yang, Peiran; Kuc, Rhoda E.; Nyimanu, Duuamene; Williams, Thomas L.; Glen, Robert C.; Holt, Lucy J.; Arulanantham, Haren; Smart, Andrew; Davenport, Anthony P.; Maguire, Janet J.
Abstract: The apelin receptor is a potential target in the treatment of heart failure and pulmonary arterial hypertension where levels of endogenous apelin peptides are reduced but significant receptor levels remain. Our aim was to characterise the pharmacology of a modified peptide agonist, MM202, designed to have high affinity for the apelin receptor and resistance to peptidase degradation and linked to an anti‐serum albumin domain antibody (AlbudAb) to extend half‐life in the blood. In competition, binding experiments in human heart MM202‐AlbudAb (pKi = 9.39 ± 0.09) bound with similar high affinity as the endogenous peptides [Pyr 1 ]apelin‐13 (pKi = 8.83 ± 0.06) and apelin‐17 (pKi = 9.57 ± 0.08). [Pyr 1 ]apelin‐13 was tenfold more potent in the cAMP (pD2 = 9.52 ± 0.05) compared to the β‐arrestin (pD2 = 8.53 ± 0.03) assay, whereas apelin‐17 (pD2 = 10.31 ± 0.28; pD2 = 10.15 ± 0.13, respectively) and MM202‐AlbudAb (pD2 = 9.15 ± 0.12; pD2 = 9.26 ± 0.03, respectively) were equipotent in both assays, with MM202‐AlbudAb tenfold less potent than apelin‐17. MM202‐AlbudAb bound to immobilised human serum albumin with high affinity (pKD = 9.02). In anaesthetised, male Sprague Dawley rats, MM202‐AlbudAb (5 nmol, n = 15) significantly reduced left ventricular systolic pressure by 6.61 ± 1.46 mm Hg and systolic arterial pressure by 14.12 ± 3.35 mm Hg and significantly increased cardiac contractility by 533 ± 170 mm Hg/s, cardiac output by 1277 ± 190 RVU/min, stroke volume by 3.09 ± 0.47 RVU and heart rate by 4.64 ± 2.24 bpm. This study demonstrates that conjugating an apelin mimetic peptide to the AlbudAb structure retains receptor and in vivo activity and may be a new strategy for development of apelin peptides as therapeutic agents.